Social correlates of cigarette smoking among Icelandic adolescents: A population-based cross-sectional study - Kristjansson, Alfgeir L (BioMed Central, 2008)
BACKGROUND: Previous research has shown that between 80 and 90 percent of adult smokers report having started smoking before 18 years of age. Several studies have revealed that multiple social factors influence the likelihood of smoking during adolescence, the period during which the onset of smoking usually occurs. To better understand the social mechanisms that influence adolescent smoking, we analyzed the relationship and relative importance of a broad spectrum of social variables in adolescent smoking in Iceland, a Nordic country with high per-capita income. METHODS: We used cross-sectional data from 7,430 14- to 16 year-old students (approximately 81% of all Icelanders in these age cohorts) in the 2006 Youth in Iceland study. The Youth in Iceland studies are designed to investigate the role of several cognitive, behavioral, and social factors in the lives of adolescents, and the data collected are used to inform the design, implementation, and evaluation of substance use prevention programs that are being developed by Icelandic social scientists, policy makers, and practitioners. RESULTS: Our analysis revealed that friends' smoking behavior and attitude toward smoking were strongly associated with adolescent smoking and other tobacco use, as well as alcohol consumption during the previous 30 days. Main protective factors were parent's perceived attitude toward smoking, the quantity of time spent with parents, absence of serious verbal conflict between parents and adolescents, and participation in physical activity. Family structure was related to adolescent smoking to a small extent, but other background factors were not. CONCLUSION: We conclude that multiple social factors are related to adolescent smoking. Parents and other primary preventive agents need to be informed about the complicated nature of the adolescent social world in order to maximize their impact.